Dual Illumination Planar Doppler Velocimetry using a Single Camera - Charrett, Thomas O. H.; Ford, Helen D.; Nobes, David S.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2003)
A Planar Doppler Velocimetry (PDV) illumination system has been designed which is able to generate two beams, separated in frequency by about 600 MHz. This allows a common-path imaging head to be constructed, using a single imaging camera instead of the usual camera pair. Both illumination beams can be derived from a single laser, using acousto-optic modulators to effect the frequency shifts. One illumination frequency lies on an absorption line of gaseous iodine, and the other just off the absorption line. The beams sequentially illuminate a plane within a seeded flow and Doppler-shifted scattered light passes through an iodine vapour cell onto the camera. The beam that lies at an optical frequency away from the absorption line is not affected by passage through the cell, and provides a reference image. The other beam, the frequency of which coincides with an absorption line, encodes the velocity information as a variation in transmission dependent upon the Doppler shift. Images of the flow under both illumination frequencies are formed on the same camera, ensuring registration of the reference and signal images. This removes a major problem of a two-camera imaging head, and cost efficiency is also improved by the simplification of the system. The dual illumination technique has been shown to operate successfully with a spinning disc as a test object. The benefits of combining the dual illumination system with a three-component, fibre-linked imaging head developed at Cranfield will be discussed.
Keywords: Acousto-optic frequency switching; Flow measurement; Planar Doppler Velocimetry